Mathematics

posted by .

How would you solve for:
(the square root of 7-the square root of 3)^2

^=the power of

[sqrt(7) - sqrt(3)]^2 =

7 + 3 - 2sqrt(21) = 10 - 2sqrt(21)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math calculus please help!

    l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
  2. math

    determine the area of triangle abc when side ab= square root of x, side bc= square root of x, and side ca= the square root of the square root of x. So how do I solve it. How do I add the square root of x + the square root of x + the …
  3. math

    thanks for the help but i was wondering (16 square root of x-3) times(square root of x-1) is equal to 16x-19 square root of x then plus 3 No, it is not. 16 (sqrt (x-3) ) (sqrt (x-1)) if that is your problem. It is hard to determine …
  4. Math

    How do you find a square root of a number that's not a perfect square?
  5. calc check: curve length

    Find the length of the curve y=(1/(x^2)) from ( 1, 1 ) to ( 2, 1/4 ) [set up the problem only, don't integrate/evaluate] this is what i did.. let me know asap if i did it right.. y = (1/(x^2)) dy/dx = (-2/(x^3)) L = integral from a …
  6. algebra

    simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 + 7 …
  7. Algebra

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
  8. Algebra - sqrts

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
  9. algebra 2

    Not sure if either one of these answer are correct to simplify the sqrt for 24 1) 24 = 6 x 4 square root of 24 = square root of 6 x 4 2 root 6 2) sq root 24 = sq root (4x6)= sqrt 4 x sqrt 6= 2sq root 6=4.89898 3) Square root of 24 …
  10. algebra

    Which shows the expressions in the order they would appear on a number line from least to greatest?

More Similar Questions